PERAN BADAN USAHA MILIK DESA (BUMDES) TERHADAP PEMBERDAYAAN MASYARAKAT DESA TRIDANA MULYA KECAMATAN LANDONO KABUPATEN KONAWE SELATAN - Wijaya, Sebrian Hari; Sartono, Sartono; Yusuf, Muhammad (REZ PUBLICA, 2020)
This study aims to determine the Role of Village-Owned Enterprises (BUMDES) on Community Empowerment in Tridana Mulya Village, Landono District, Konawe Selatan Regency. The research method used in this research is descriptive qualitative. The data obtained from interviews, observation and documentation. The results show that the role of village-owned enterprises is always communicative and responsive to subordinates so that the implementation of service tasks can be carried out properly by providing the widest possible opportunity for village officials to be actively involved in the process of achieving goals. BUMDES and people who need credit for saving and loan capital sometimes communicate ineffective. Community Empowerment with the strengthening of community institutions in the village of Tridana Mulya so that the community can easily channel their aspirations so that their needs can be identified and followed up by community participation in the economic development process in empowering the community and encouraging the independence of the village community.